A case series of three patients with unilateral disconnected pulmonary artery supplied by an ipsilateral patent ductus arteriosus: neonatal ductal stenting as palliation to preserve pulmonary arterial patency. Issue 6 (18th November 2020) - Ho, Andrew B; Salmon, Tony P; Hribernik, Ines; Hayes, Nicholas; Thomson, John D; Bentham, James R
Abstract: Background : Disconnected branch pulmonary arteries with a systemic arterial origin of the disconnected vessel is a rare, but well-described entity. Most will have ductal tissue connecting the pulmonary artery to the aorta. Case summary : We describe in this paper the haemodynamic result in three neonates presenting with ductal origin of a single branch pulmonary artery in the context of trans-catheter stenting procedures to maintain or re-recruit vessel patency. All were faced with potential or actual ductal closure and proceeded to trans-catheter stenting to re-cannalate the duct-dependent pulmonary artery. Two patients with otherwise normal anatomy struggled post-procedure with pulmonary hypertension and right ventricular dilatation. Both required surgical re-anastomosis of the disconnected pulmonary artery during the same admission—one 26 days post-stenting following failure to wean from high-flow respiratory support and the second 8 days post-stenting following failed extubation. In contrast, a patient with tetralogy of Fallot born at 2.5 kg underwent sequential stenting of the right ventricular outflow tract and then the left-sided ductus. He had a good post-procedural course and thrived for several months before complete repair. Discussion : We describe the clinical courses and discuss the resultant haemodynamics, highlighting the importance of flow to each lung, the resulting haemodynamic implications and the compounding effects of additional lesions.